2018
DOI: 10.3389/fneur.2018.00244
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Cluster Analysis of Semicircular Canal and Otolith Deficits in Bilateral Vestibulopathy

Abstract: BackgroundGait imbalance and oscillopsia are frequent complaints of bilateral vestibular loss (BLV). Video-head-impulse testing (vHIT) of all six semicircular canals (SCCs) has demonstrated varying involvement of the different canals. Sparing of anterior-canal function has been linked to aminoglycoside-related vestibulopathy and Menière’s disease. We hypothesized that utricular and saccular impairment [assessed by vestibular-evoked myogenic potentials (VEMPs)] may be disease-specific also, possibly facilitatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
3
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 38 publications
2
30
3
4
Order By: Relevance
“…vHIT measuring function of each SCC) does not predict fall risk, whereas specific patterns of vestibular impairment could be associated with higher fall risk. For example, the disease specific sparing of the anterior SCC, which is described by previous studies [28,30] in BV patients with aminoglycosides toxicity, might be associated with a different fall risk depending on otolith function. However, given the wide range of patterns of vestibular impairment, this would lead to too small sample size groups for statistical analyses.…”
Section: Vestibular Tests and Fall Riskmentioning
confidence: 89%
See 1 more Smart Citation
“…vHIT measuring function of each SCC) does not predict fall risk, whereas specific patterns of vestibular impairment could be associated with higher fall risk. For example, the disease specific sparing of the anterior SCC, which is described by previous studies [28,30] in BV patients with aminoglycosides toxicity, might be associated with a different fall risk depending on otolith function. However, given the wide range of patterns of vestibular impairment, this would lead to too small sample size groups for statistical analyses.…”
Section: Vestibular Tests and Fall Riskmentioning
confidence: 89%
“…Recent studies have shown the wide variety of patterns of vestibular impairment in BV patients [30]. It is conceivable that one single vestibular test evaluating one single vestibular sensor (e.g.…”
Section: Vestibular Tests and Fall Riskmentioning
confidence: 99%
“…32 Recent studies have also shown that the results of VEMPs may depend on the etiology of BVD: oVEMP abnormalities are more frequent in BVD due to inner ear infection and aminoglycoside ototoxicity than in BVD due to MD. 6,34…”
Section: Vestibular Evoked Myogenic Potentialsmentioning
confidence: 99%
“…1,2 Patients with BVD mostly present with dizziness, oscillopsia, and unsteadiness, mostly during locomotion. [3][4][5][6] BVD accounts for 4 to 7% of dizziness/vertigo. 3,[7][8][9] The prevalence of BVD is estimated at 28 per 100, 000 persons in the United States.…”
mentioning
confidence: 99%
“…For example, inner ear infections and aminoglycoside vestibulotoxicity affect both SCC and otolith organ function more often, whereas in bilateral Meniere's disease, they affect SCC function but much less so otolith function. 57 In time, such patterns may help improve diagnostic accuracy.…”
Section: Clinical Application Of Video Head Impulse Test Peripheral Vmentioning
confidence: 99%